從實務社群談課程發展與教師專業發展Cultivating Communities of Practice for Curriculum Development and Teacher Professional Development - 王為國Wei-Kuo Wang (Higher Education Foundation, 2007)
個人主義之教師文化會阻礙彼此的交流與互動，不利於知識的創新。近幾年來，教育界有關實務社群的探討愈來愈多，認為可以增進教師彼此之間的互動與創新。本文從實務社群的角度出發，探討其對課程發展及教師專業發展的啟示。在課程發展方面，實務社群可以協助教師發展新課程、協助教師覺醒課程理論、幫助教師累積課程實務知識、協助教師解決課程的問題等。至於在教師專業發展方面，實務社群可以促進教師學習、提供教師學習機會、激發教師專業熱情、激發教師學習動機、促進教師專業知能、幫助學校招募及留住人才、協助輔導新手教師、塑造學校積極的文化、建立多元化溝通管道等。學校應該給與教師足夠的時間與空間去發展實務社群，如此，實務社群對於課程發展及教師專業發展的貢獻才能夠彰顯出來，並且進一步提升學校的教育品質。 The individualism teacher culture obstructs the communication and interaction of teachers and knowledge innovation. The discussions of communities of practice applying to schools have increased noticeably in recent years. This paper investigates curriculum development and teacher professional development by the point of view of communities of practice. In curriculum development, communities of practice can facilitate teachers in developing a new curriculum, aid teachers being aware of curriculum theory, help teachers with accumulating curriculum practice knowledge, and assist teachers in solving curriculum problems. In teacher professional development, communities of practice can advance teachers learning, afford teachers with learning opportunities, encourage professional passion of teachers, excite learning motivation of teachers, improve professional competences of teachers, help school with recruiting and remaining teachers, guide novice teachers, shape the positive cultural in school, and construct multiple communication paths. The school should give teachers enough time and space for developing communities of practice, thus communities of practice can contribute to curriculum practices and teacher professional development, furthermore they can promote the quality of the school.